Malta : Financial Sector Assessment Program-Technical Note-Insurance and Securities Sector Supervision. (IMF Staff Country Reports; Country Report ;, 2019)
This technical note reviews the institutional arrangement and supervisory practices for the insurance and securities sectors in Malta, focusing on supervisory effectiveness. The legal powers and supervisory objectives of the Malta Financial Services Authority (MFSA) are clear and in line with international standards. The MFSA has adequate legal authority to discharge its supervisory responsibilities and to take the necessary preventive and corrective measures to protect the public interest. Clearly established legal gateways for information sharing facilitate supervisory coordination and cooperation between the MFSA and relevant supervisors/authorities, domestically and internationally. For the avoidance of doubt, the MFSA has proposed amending the MFSA Act to explicitly include the promotion of financial stability and financial market integrity as one of its key functions. Stable funding and full autonomy over the recruitment process are needed to support the MFSA's operational and financial independence. Recognizing the scope for harmonizing and enhancing the current sectoral risk-based supervision frameworks (RBSF), the MFSA is developing an integrated RBSF.